Rechallenge with anti-EGFR therapy to extend the continuum of care in patients with metastatic colorectal cancer - Cremolini, Chiara; Montagut, Clara; Ronga, Philippe; Venturini, Filippo; Yamaguchi, Kensei; Stintzing, Sebastian; Sobrero, Alberto (Frontiers in Oncology, 2023)
In patients with RAS wild-type metastatic colorectal cancer (mCRC), an anti-epidermal growth factor receptor (EGFR) monoclonal antibody plus chemotherapy is a standard option for treatment in the first-line setting. Patients who progress while on treatment with anti-EGFR-based therapy can be resistant to further anti-EGFR treatment, but evidence suggests that the anti-EGFR-resistant clones decay, thereby opening the potential for rechallenge or reintroduction in later lines of treatment. Results from recent clinical studies have shown that some patients with mCRC who are rechallenged with anti-EGFR monoclonal antibodies exhibit durable responses. While other therapies have demonstrated improved overall survival in chemorefractory mCRC over the past decade, rechallenge with anti-EGFR monoclonal antibodies in later lines of treatment represents a new option that deserves further investigation in clinical trials. In this review, we summarize the molecular rationale for rechallenge or reintroduction in patients with mCRC who have progressed on earlier-line anti-EGFR treatment and examine the current evidence for using liquid biopsy as a method for selecting rechallenge as a therapeutic option. We also provide an overview of published trials and trials in progress in this field, and outline the potential role of rechallenge in the current clinical setting.